PTU-099 A novel functional bioassay predicts 90-day survival in patients with severe alcoholic hepatitis. (17th June 2017) - Yates, E; Cramp, M; Dhanda, A
Abstract : Introduction: Severe alcoholic hepatitis (SAH) has a high mortality and only corticosteroids have a proven short term benefit. Early prediction of treatment response would allow selection of appropriate patients who would benefit from corticosteroids. We have previously reported that a functional bioassay measuring in vitro corticosteroid sensitivity, DILPA, accurately predicts 6 month survival in patients with SAH 1 . However, due to its requirement for radiation it lacked clinical translatability and a second generation assay, bromodeoxyuridine (BrdU) incorporation in lymphocyte steroid sensitivity assay (BLISS) assay, has been developed and validated in healthy controls 2 . In this study we aimed to generate preliminary data to determine whether the BLISS assay can be used to predict clinical outcome in patients with SAH. Method: Peripheral blood was drawn from patients with a clinical diagnosis of SAH (discriminant function [DF] >32). All participants gave informed consent and ethical approval was obtained from the NHS Health Research Authority. All patients were treated with corticosteroids for 28 days. The primary outcome measure was 90 day survival. Peripheral blood mononuclear cells, isolated by density gradient centrifugation, were stimulated with lymphocyte mitogen in the absence or presence of dexamethasone and cultured for 48 hours per previously described protocol 2 . Proliferation was determined by measuring BrdU incorporation using a commercial kit. The maximum suppression of proliferation by corticosteroids (Imax) was determined. Results: 10 patients were recruited (7 female, median age 50) with mean DF 75. 6 patients survived to 90 days and had a significantly higher Imax than non-survivors (27% v −12%; p=0.01) with clear separation between groups (figure 1). Survivors also had lower Lille score than non-survivors (0.20 v 0.79; p=0.02) but in applying the established threshold of 0.45, 1 patient was misclassified as a steroid non-responder. However, Imax did not correlate with Lille score (r 2 =0.21) or percentage change in bilirubin from day 0 to day 7 (r 2 =0.10). Conclusion: The BLISS assay clearly differentiates survivors from non-survivors at 90 days and shows potential for use as a stratification tool in the initial management of patients with SAH. Further validation in a larger multicentre cohort is planned. References: . Dhanda, di Mambro, Hunt, McCune, Dayan, Dick, Lee, Collins. Long-term outcome in patients with severe alcoholic hepatitis can be reliably determined using an in vitro measure of steroid sensitivity. Hepatology2015; 61: 1099 . Williams, Stimpson, Collins, Enki, Sinha Lee, Dhanda. Development and validation of a novel bioassay to determine glucocorticoid sensitivity. Biomarker Research 2016; 4: 26 Disclosure of Interest: None Declared